Desempenho produtivo e respostas hematológicas da Tilápia- do-Nilo submetida a diferentes níveis de proteína e condições de estresse - Freitas, Jakeline Marcela Azambuja de [UNESP] (2015)
This research aimed to evaluate the digestibility coefficients and growth performance of Nile tilapia fed diets containing levels of digestible protein (DP) of 22.1, 25.6, 28.6, 31.9 and 33.9%, as well as evaluate the metabolic and nutritional condition of fish by determining the activity of key enzymes of intermediary metabolism. We used 440 fingerlings (9.27 ± 0.22 g), randomly distributed in 40-250 L aquaria, and fed for 110 days with experimental diets. The experimental design was entirely randomized with five treatments and eight replicates. At the end of feed trial we evaluate growth parameters and feed efficiency, as also collected samples of liver and muscle to evaluation of enzyme activity and proximate composition of tissues. Final weight, weight gain and feed efficiency were lower (P<0.05) for fish fed diet containing 22.1% DP. Contrary effect was observed for feed intake, lipids and energy. Whole-body crude energy and lipid content were higher (P<0.05) for fish fed diets containing 22.1 and 28.6% DP while whole-body protein content was higher (P<0.05) for fish fed diets containing 31.9 and 33.9% DP. Digestibility coefficients of dry matter and crude protein were higher (P<0.05) for diets containing 22.1 and 25.6% DP. Regarding to crude protein was observed lower coefficients for level of 28.6% DP. Fish fed diets containing 33.9% DP showed higher (P<0.05) concentration of hepatic protein while lipids and glycogen were higher (P<0.05) for fish fed diets containing lower protein (22.1%). Activity of key enzymes of amino acid catabolism (ALT and GDH) and gluconeogenesis (FBPase) was higher (P<0.05) for diets of high protein (33.9 and 33.9%). Lipogenesis (ME), glycolysis (HK-IV and HK) and pentose phosphate pathway (G6PD) were stimulated (P<0.05) with the reduction of DP. Digestible protein requirement for Nile tilapia was estimated to be 29.2%, agreeing with the values established for this ...